Conservation voltage regulation at residential level - Silva, Rafael (2018)
The continued growth of the world energy consumption requires the implementation of new and effective energy strategies, targeted to enhance the transition toward low-carbon technologies, where energy efficiency and renewable energies play a major role. In order to cope within this scenario, an intelligent integration in electrical energy infrastructure, called Smart Grids, allows the implementation of the Conservation Voltage Regulation (CVR) technique, which is based on the premise that reduction of the supplier voltage will lead to reduced energy consumption by final consumers without harming their appliances. This work aims to evaluate the power consumption reduction due to CVR implementation and its economic viability at residential level. Several experimental tests were carried out on residential appliances, including lighting systems, liquid-crystal-display televisions, washing machines, air-conditioning devices, fridges and laptop computers. To quantify the energy savings achieved by the CVR implementation for each of the mentioned equipment, it was used the CVR factor, fCVR, which measures the ratio between energy savings and voltage reduction. This quantitative indicator has typical values between 0,4 and 1,0, and may take values higher than 1,0 in the case of resistive loads, upon how long they are in operation. The obtained results validate the implementation of CVR technique at residential level, indicating a considerable energy and money savings for final consumers.